(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
An intensive floristic investigation provides the first systematic and comprehensive account of the floral diversity of Baraiyadhala National Park of Bangladesh, and recognizes 528 wild taxa belonging to 337 genera and 73 families (Magnoliids and Eudicots) in the park. Habit analysis reveals that trees (179 species) and herbs (174 species) constitute the major categories of the plant community followed by shrubs (95 species), climbers (78 species), and two epiphytes. Status of occurrence has been assessed for proper conservation management and sustainable utilization of the taxa resulting in 165 (31.25%) to be rare, 23 (4.36%) as endangered, 12 (2.27%) as critically endangered and 4 species (0.76%) are found as vulnerable in the forest. Fabaceae is the dominant family represented by 75 taxa, followed by Rubiaceae (47 taxa), Malvaceae (28 species), Asteraceae (27 species) and Euphorbiaceae (24 species). Twenty-three families represent single species each in the area.